Comparative and Quantitative Myology of the Forearm and Hand of Prosimian Primates. Issue 8 (6th June 2013) - Gyambibi, Akua; Lemelin, Pierre
ABSTRACT Associations between the relative development of muscles of the forearm and hand of prosimian primates and locomotor behavior, body size, and grasping specializations have been made on the basis of qualitative observations. These associations are here tested through comparative and quantitative analyses of muscle mass data for a broad sample of prosimian species (i.e., strepsirrhines and tarsiers). The musculature of the forearm and hand of 17 fresh‐frozen specimens representing six families and 12 species was dissected and weighed. Muscle weights were scaled relative to body mass of individual specimens using regression and compared by limb compartment and functional group. Forearm and digital flexor muscle masses are highly correlated with body mass (r = 0.97 and r = 0.96, respectively) and scale isometrically. As a general trend within the prosimian sample, the relative mass of the flexor compartment increases with body size. Interspecific comparisons of functional groups of muscles did not identify any association between larger muscle mass and locomotor adaptations or grasping specializations of the hand. However, compared to other prosimians, the adductor pollicis muscle of Nycticebus is more developed (52% of the intrinsic hand musculature sampled) and the flexor digitorum profundus muscle has two well‐separated heads with more individualized tendons, with the pollex and digit IV receiving tendinous contributions from both muscle heads. These differences that characterize the forearm and hand of Nycticebus correlate with the extreme thumb divergence and pincer‐like grips of lorises. Anat Rec, 2013. © 2013 Wiley Periodicals, Inc.